Wind turbines in managed forests partially displace common birds. (15th February 2023) - Rehling, Finn; Delius, Anna; Ellerbrok, Julia; Farwig, Nina; Peter, Franziska
Abstract: Wind turbines are increasingly being installed in forests, which can lead to land use disputes between climate mitigation efforts and nature conservation. Environmental impact assessments precede the construction of wind turbines to ensure that wind turbines are installed only in managed or degraded forests that are of potentially low value for conservation. It is unknown, nevertheless, if animals deemed of minor relevance in environmental impact assessments are affected by wind turbines in managed forests. We investigated the impact of wind turbines on common forest birds, by counting birds along an impact-gradient of wind turbines in 24 temperate forests in Hesse, Germany. During 860 point counts, we counted 2231 birds from 45 species. Bird communities were strongly related to forest structure, season and the rotor diameter of wind turbines, but were not related to wind turbine distance. For instance, bird abundance decreased in structure-poor (−38%) and monocultural (−41%) forests with wind turbines, and in young (−36%) deciduous forests with larger and more wind turbines (−24%). Overall, our findings suggest that wind turbines in managed forests partially displace common forest birds. If these birds are displaced to harsh environments, wind turbines might indirectly contribute to a decline of their populations. Yet, forest bird communities are locally more sensitive to forest quality than to wind turbine presence. To prevent further displacement of forest animals, forests of lowest quality for wildlife should be preferred in spatial planning for wind turbines, for instance small and structure-poor monocultures along highways. Highlights: Little is known about whether wind turbines displace common forest birds. Bird abundance was related to forest quality, but not to wind turbine distance. Across sites, larger and more wind turbines were associated with bird displacement. The most degraded forests should be prioritized in spatial planning of wind turbines.